Exploring the Use of Informative Speaking Strategy at English Hour Program at RRI Pro 2 Banjarmasin - Riskina, Aulia; Al Farhan, Miftah; Aflahah, Noor Aida (English Department of Faculty of Tarbiyah and Teacher Training, 2024)
Informative speaking involves delivering speeches to disseminate knowledge and improve the audience's understanding of specific topics. Therefore, this study aims to explore the use of informative speaking strategies in the English Hour programme at RRI PRO 2 Banjarmasin, focusing on how broadcasters implement these strategies and the challenges they face. The case study method was used to obtain data using in-depth interviews, observation, and analysis of documentation in the broadcast process. Two broadcasters who handle the English Hour programme were involved as research participants. The results of data collection were processed using data analysis techniques such as data condensation, data display and conclusion drawing. The results identified that broadcasters used several strategies, such as topic selection, in-depth research, organised structure, clear language, relevant examples, and an engaging delivery style. In addition, the barriers they faced were delivering complex topics, translating terms, and maintaining the flow of the conversation during live broadcasts. In addition, further research is highly recommended to dig deeper into the effectiveness of this strategy and explore additional methods to improve informative speaking in radio broadcasts.